A questionnaire development to assess the social representation of nurses in the Basque Country: a psychometric assessment - Tíscar-González,Verónica; Iturregui-Mardaras,Leire; Miranda-Bernabé,Eztizen; Bermúdez-Ampudia,Cristina; Cidoncha-Moreno,Maria Ángeles; Ballesteros-Peña,Sendoa (PeerJ, 2022)
Background Only a few Spanish studies have explored how nurses are seen by society and no validated tools exist for this purpose in the scientific literature. Objectives The aim was create and evaluate the psychometric characteristics of a questionnaire that explored the social representation of nursing in social and health care. Methods Qualitative and quantitative methods were used to develop the questionnaire and the first version was created based on existing studies. A three-round Delphi technique was used that involved nurses, doctors, journalists and a politician. The pilot questionnaire was then tested and retested with 23 journalism students, with an interval of 10–14 days between the two phases. After further modifications, the questionnaire was sent to all the third and fourth year journalism students at the University of the Basque Country. Principal component factor analysis was used to identify the key components for the questionnaire. Results A total of 141 third and fourth year journalism students took part in the study. The internal consistency of the 43-item perception section of the questionnaire had a Cronbach’s alpha value of 0.90. The 42.7% agreed or strongly agreed that nursing was an eminently scientific profession and 26.3% agreed or strongly agreed with the statement that nurses were presented in the media as health educators and disseminators. Just under a fifth (19.9%) agreed with the statement that society was aware of the competencies that nurses required. Conclusions The questionnaire provided the first validated tool that allowed researchers to assess how nursing, and all of its areas of professional development, were perceived by society. This could enable studies to assess the evolution of the profession over time and between different socio-cultural contexts.
Keywords: Nursing; Journalism; Social; Nursing now